PENGARUH KONDISI SOSIAL EKONOMI ORANG TUA TERHADAP MOTIVASI MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI PADA SISWA KELAS XII SMA NEGERI 10 PEKANBARU - Susilawati Susilawati; Suarman Suarman; Hendripides Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problems that will be examined in this study are: 1) Is there a significant influence on the level of parents' income on the motivation to continue tertiary education for class XII students, 2) Is there a significant effect on the level of parental education on the motivation to continue education to higher education in grade students XII, 3) Is there a significant influence on the socio-economic conditions of parents on the motivation to continue their education to tertiary education for class XII students. The population in this study were all class XII SMA 10 Pekanbaru starting from social studies class 1- 4 and MIPA 1- 4. The sample of this study was students of SMA Negeri 10 Pekanbaru which consisted of 281 students reduced to 97 students using the Isaac and Michael samples with their level of error. 5% sampling technique using random sampling. Primary data obtained by distributing questionnaires in the form of Google Forms to each class. In this study the data were collected and then analyzed using multiple linear regression analysis. The results of the regression analysis obtained the equation Y = 18.923 + 0.301 + 0.751. Test the meaning of the regression equation with the F test, obtained Fcount = 9,884 with a probability of 0.00 and less than 0.05. This means that there is a significant influence on the socio-economic conditions of parents on the motivation to continue their education to tertiary institutions for class XII students of SMA Negeri 10 Pekanbaru.Key Words : Socioeconomic conditions, motivation